Development and Study of Biocompatible Polyurethane-Based Polymer-Metallic Nanocomposites - Csarnovics I (Dove Medical Press, 2020)
István Csarnovics,1 Julia Burunkova,2 Danara Sviazhina,2 Evgeniy Oskolkov,2 George Alkhalil,2 Elena Orishak,3 Ludmila Nilova,3 István Szabó,1 Péter Rutka,1 Krisztián Bene,4 Attila Bácsi,4 Sándor Kökényesi1 1Institute of Physics, Faculty of Science and Technology, University of Debrecen, Debrecen, Hungary; 2International Scientific and Research Institute of Bioengineering, School of Photonics, ITMO University, St., Petersburg, Russian Federation; 3Department of Medical Microbiology, Faculty of Preventive Medicine, North-Western State Medical University Named After I.I. Mechnikov, St., Petersburg, Russian Federation; 4Department of Immunology, Faculty of Health, University of Debrecen, Debrecen, HungaryCorrespondence: István CsarnovicsUniversity of Debrecen, Faculty of Science and Technology, Institute of Physics, Bem sq 18/a, Debrecen 4026, HungaryEmail csarnovics.istvan@science.unideb.huIntroduction: In this work we selected components, developed technology and studied a number of parameters of polymer nanocomposite materials, remembering that the material would have high optical and good mechanical characteristics, good sorption ability in order to ensure high value of the optical signal for a short time while maintaining the initial geometric shape. In addition, if this nanocomposite is used for medicine and biology (biocompatible or biocidal materials or the creation of a sensor based on it), the material must be non-toxic and/or biocompatible. We study the creation of polymer nanocomposites which may be applied as biocompatible materials with new functional parameters.Material and Methods: A number of polymer nanocomposites based on various urethane-acrylate monomers and nanoparticles of gold, silicon oxides, zinc and/or titanium oxides are obtained, their mechanical (microhardness) properties and wettability (contact angle) are studied. The set of required, biology-related properties of these materials, such as toxicity and sorption of microorganisms are also investigated in order to prove their possible applicability.Results and Discussion: The composition of the samples influences their microhardness and the value of contact angle, which means that varying with the monomer and the metallic, oxide nanoparticles composition, we could change these parameters. Besides it, the set of required, biology-related properties of these materials, such as toxicity and sorption of microorganisms were also investigated in order to prove their possible applicability. It was shown that the materials are non-toxic, the adhesion of microorganisms on their surface also could be varied by changing their composition.Conclusion: The presented polymer nanocomposites with different compositions of monomer and the presence of nanoparticles in them are prospective material for a possible bio-application as it is biocompatible, not toxic. The sorption of microorganism could be varied depending on the type of bacterias, the monomer composition, and nanoparticles.Keywords: polymer nanocomposites, metallic nanoparticles, oxide nanoparticles, biocompatible materials, microhardness